Effects of losartan on expression of monocyte chemoattractant protein-1 (MCP-1) in hyperuricemic nephropathy rats. (3rd September 2015) - Yu, Shengyou; Ren, Qi; Wu, Wei
Abstract: The monocyte chemoattractant protein-1 (MCP-1) plays an important role in the pathogenesis of progression of renal failure. This is based on the observations done both in various animal models of renal damage and in different types of human renal disease. During the development of non-infectious kidney stones, crystals are formed and deposited on the kidneys and the kidneys are surrounded by monocytes/macrophages. We have proposed that in response to crystal exposure, renal epithelial cells produce chemokines, which attract the monocytes/macrophages to the sites of crystal deposition. In this study, we investigated the expression of MCP-1 protein by SD rats exposed to oxonic acid (OA). Our study showed that hyperuricemia accelerates renal progression via a mechanism linked to high MCP-1 which may mediate the inflammation reaction of renal diseases induced by hyperuricemia. Losartan may retard the progression of advanced renal dysfunction, and the mechanism was partly due to blocking of renal inflammation induced by the uric acid. Because the number of experiments performed here is very few, results must be confirmed by more extensive studies with a larger sample size.